Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0169038
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 R132H Mutation Enhances Cell Migration by Activating AKT-mTOR Signaling Pathway, but Sensitizes Cells to 5-FU Treatment as NADPH and GSH Are Reduced

Abstract: Aim of studyMutations of isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) gene were recently discovered in vast majority of World Health Organization (WHO) grade II/III gliomas. This study is to understand the effects of IDH1 R132H mutation in gliomagenesis and to develop new strategies to treat glioma with IDH1 R132H mutation.Materials and methodsOver expression of IDH1 R132H in U87MG cells was done by transfecting cells with IDH1 R132H plasmid. MTT assay, scratch repair assay and western blot were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…This effect of rapamycin treatment highlights the importance of mTOR activity in malignant phenotype of IDH1 mutant cells. Our results – concerning the potential roles of mTOR activity and 2-HG production in migration of malignant cells – confirm the recently published data about the enhanced migration capacity of mIDH1 transfected glioma cells [45]. Only this study and our work show the potential benefit of mTOR inhibitors on the migration of IDH mutation related malignant cellular phenotype, in this context.…”
Section: Discussionsupporting
confidence: 91%
“…This effect of rapamycin treatment highlights the importance of mTOR activity in malignant phenotype of IDH1 mutant cells. Our results – concerning the potential roles of mTOR activity and 2-HG production in migration of malignant cells – confirm the recently published data about the enhanced migration capacity of mIDH1 transfected glioma cells [45]. Only this study and our work show the potential benefit of mTOR inhibitors on the migration of IDH mutation related malignant cellular phenotype, in this context.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we report the first case of Maffucci syndrome associated SCH that was managed successfully using mTOR inhibitor as a concurrent medical therapy with surgery (Riou et al, 2012 Zhu et al (2017) has demonstrated that overexpression of mutated IDH1, increases cell migration and enhances AKT-mTOR signaling. These results support the use of mTOR inhibitor to target rapid vascular proliferation in Maffucci patients carrying IDH1 mutations.…”
Section: Disease Progression Nonementioning
confidence: 99%
“…Confirmatory diagnosis for that case could not be made as mutation of IDH gene was not detected. Recent in vitro study by Zhu et al () has demonstrated that overexpression of mutated IDH1 , increases cell migration and enhances AKT–mTOR signaling. These results support the use of mTOR inhibitor to target rapid vascular proliferation in Maffucci patients carrying IDH1 mutations.…”
Section: Reported Vascular Anomalies In Maffucci Syndrome and Clinicamentioning
confidence: 99%
“…IDH mutation sensitizes glioma cells to cytotoxic agents such as 5‐FU treatment through the reduction of antioxidants (NADPH and GSH) by mutant IDH , and to poly‐adenosine diphosphate ribose polymerase inhibition via inducing a mutant IDH ‐dependent homologous recombination defect (Fig. ) . From the metabolic viewpoint, mutant IDH1 lowered NAD + levels by downregulating the NAD + salvage pathway enzyme nicotinate phosphoribosyltransferase (NAPRT1), sensitizing to NAD + depletion via concomitant nicotinamide phosphoribosyltransferase (NAMPT) inhibition, identifying NAD + depletion as a metabolic susceptibility of IDH1 mutant cancers (Fig.…”
Section: Molecular Therapies Targeting Mutation‐dependent Metabolism mentioning
confidence: 99%
“…5). 60,61 From the metabolic viewpoint, mutant IDH1 lowered NAD + levels by downregulating the NAD + salvage pathway enzyme nicotinate phosphoribosyltransferase (NAPRT1), sensitizing to NAD + depletion via concomitant nicotinamide phosphoribosyltransferase (NAMPT) inhibition, identifying NAD + depletion as a metabolic susceptibility of IDH1 mutant cancers (Fig. 5).…”
Section: Molecular Therapies Targeting Mutation-dependent Metabolism mentioning
confidence: 99%